Biostratigraphy and Paleobathimetry Microfossil Foraminera in the Sentolo Formation on the Jambon Line, Bantul Regency, Special Region of Yogyakarta Province - Citayana Fani Refalta; Donan Satria Yudha; Didit Hadi Barianto (Journal of Tropical Biodiversity and Biotechnology, 2022)
Foraminifera microfossils can be used to determine the age of rocks and the depositional environment of an area. The research location is part of Sentolo Formation. Our stratigraphic data located on the Jambon section, Bantul Regency, Special Region of Yogyakarta Province. The appearance of the research area is in the form of well-exposed and ideal cliffs and the lithology of the formation has the potential for rock content rich in foraminifera microfossils. This is the reason for the microfossil analysis of planktic and benthic foraminifera in the study area. The purpose of this study is to determine the age and depositional environment. The research method was carried out by measuring the stratigraphic sections, sampling, and doing paleontological analysis based on planktic and benthic foraminifera. The results showed that the biostratigraphy can be divided into Globigerina venezuelana Zone (N18) & the Globorotalia plesiotumida Zone (N19), as well as the paleobathimetry, belongs to upper - lower bathyal.